Optimizing the Management of the Tahfidz Learning Program at NU Islamic Elementary School: Instilling Qur'anic Values from an Early Age - Mustofa, Zaenal; Nurulloh, Ahmat (Universitas KH. Abdul Chalim Pacet Mojokerto, 2024)
The tahfidz learning program requires strict and systematic management. This is in order to achieve the goals that have been set. Tahfidz learning management can also be used to improve students' literacy competence. With the tahfidz program students will learn to read and memorize which will certainly affect student learning. This study aims to explain and analyze how the management of the tahfidz learning program at the Nahdlatul Ulama Sekaran Islamic Elementary School. Then also to find out what are the supporting and inhibiting factors in implementing the program. The method used to examine this is a qualitative method with a case study approach. The data collection used is by means of observation, interviews and documentation. Data analysis was carried out by using the Miles and Hubberman model in the form of data collection, data reduction, data exposure and drawing conclusions. The results showed 1) the management of the tahfidz learning program includes: a) planning to set goals, b) implementation by selecting the right people to carry out and c) evaluation to solve problems that arise. 2) Obstacles encountered were a) student discipline in memorizing, b) stability of student abilities and an unequal ratio of teachers. While things that support are a) good management, b) high will and support from parents so that the program can run optimally.